Optimization of a Mixture of Curcuma Dye Mixture with SiO₂ (Rice Husk Waste) to the Energy Efficiency of TiO₂ -based Solar Cells - Subagyo, Tulus; Widhiyanuriyawan, Denny; Widodo, Agung Sugeng; Wardana, I Nyoman Gede (Pandawa Institute, 2025)
Global energy challenges and environmental problems encourage the search for sustainable energy solutions, with TiO₂-based solar cells that are still limited to its efficiency due to low light absorption and charge recombination. This study aims to examine the synergistic effect of curcuma and SiO₂ dye from rice husk waste in improving the energy efficiency of TiO₂ solar cells. The research methodology involves the fabrication of sensitive solar cells with different layer compositions: TiO₂ only, TiO₂ with one layer of SiO₂ (1L-SiO₂), two layers (2L-SiO₂), and three layers (3L-SiO₂). The TiO₂ photoanode is prepared using the screen printing method, followed by loading coloring through immersion in the curcuma coloring solution. The performance of solar cells is evaluated using the current voltage measurement (I-V) and electrochemical impedance spectroscopy (EIS) to analyze efficiency, charge transportation, and recombination processes. The results show that the addition of SiO₂ increases the efficiency of solar cells, with 1L-SiO₂ producing the highest compilation of short circuit (JSC) 0.37 mA/cm², showing an increase in cargo transportation. However, 1L-SiO₂ shows a decrease in performance due to excessive thickness, which leads to an increase in charge recombination and internal resistance. Impedance analysis confirms that 1L-SiO₂ optimizes cargo transportation but also increases recombination resistance, which affects overall efficiency. Adding SiO₂ from rice husk waste increases the efficiency of TiO₂-based solar cells, with curcuma coloring increases light absorption and charge transfer. However, excessive SiO₂ layers reduce performance due to higher recombination and resistance. Further research is needed to optimize the thickness of the layer and dye stability.